2020
DOI: 10.1111/fwb.13515
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the combined effects of anticipated climate change and agricultural conservation practices on fish recruitment dynamics in Lake Erie

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 116 publications
2
18
0
Order By: Relevance
“…Thus, the ideal thermal conditions for producing high yellow perch recruitment in the west basin would be a long, cold winter followed by a rapidly warming spring. These findings are consistent with previous studies (Clady, 1976; Dippold et al., 2020; Farmer et al., 2015; Henderson & Nepszy, 1988). Controlled laboratory studies have shown that short, warm winters reduce egg size, lipid content and hatching success, lead to small larvae, and potentially alter the spawning phenology of yellow perch (Farmer et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Thus, the ideal thermal conditions for producing high yellow perch recruitment in the west basin would be a long, cold winter followed by a rapidly warming spring. These findings are consistent with previous studies (Clady, 1976; Dippold et al., 2020; Farmer et al., 2015; Henderson & Nepszy, 1988). Controlled laboratory studies have shown that short, warm winters reduce egg size, lipid content and hatching success, lead to small larvae, and potentially alter the spawning phenology of yellow perch (Farmer et al., 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the ideal thermal conditions for producing high yellow perch recruitment in the west basin would be a long, cold winter followed by a rapidly warming spring. These findings are consistent with previous studies (Clady, 1976;Dippold et al, 2020;Farmer et al, 2015;Henderson & Nepszy, 1988).…”
Section: Consistent Importance Of Abiotic Driverssupporting
confidence: 94%
See 3 more Smart Citations